ANALYSIS OF THE INFLUENCE OF INTERNATIONAL TRADE POLICY ON THE INDONESIAN ECONOMY: (Case Study when Oil Palm is discriminated in the EU) - Syifa Febriana Nurul Wildain (CURRENT ADVANCED RESEARCH ON SHARIA FINANCE AND ECONOMIC WORLDWIDE, 2022)
This study aims to determine the efforts made by Indonesia in fighting for the Indonesian palm oil industry, as well as to describe the political and business motives that are the roots of the emergence of discriminatory resolutions. The method used is a qualitative approach. The object of this research is the policies and strategies in dealing with the black palm oil campaign carried out by the European Union Parliament. The data collection technique used is the Library Research Technique. According to the findings of this study, the European Union's claims are contradictory to the facts. Research demonstrates that the European Union denies a number of facts, focusing instead on Indonesia's errors as a protectionist tool. Indonesia has the right or authority to bring this issue into the realm of international law if the results of this research can be found with certainty and can be legally accounted for.